Assessing Mathematics Teachers’ Professional Development Needs for the Merdeka Curriculum: Insights from Literature and Online Forums - Jumadi Jumadi; Lydia Lia Prayitno (Global Journal of Mathematics Education, 2025)
This study aims to analyze the training needs of mathematics teachers in implementing the Merdeka Curriculum through a systematic literature review and online focus group discussions. The background of this research is the limited readiness of teachers in understanding and applying the core principles of the Merdeka Curriculum, particularly in mathematics instruction at the junior high school level. A qualitative method was employed, combining a systematic review of relevant policy documents and journal articles with data obtained from virtual discussions involving mathematics teachers. The findings reveal that teachers require training that is practical, contextual, and grounded in classroom experiences, especially concerning differentiated instruction, formative assessment, and the integration of technology in learning. This study recommends the development of training programs tailored to teachers' actual needs and the strengthening of professional collaboration among educators to support continuous curriculum implementation.